Digital Comics Based on Don Bosco Values for Elementary School Students - Febriella Happy Agata Br Sembiring; I Gede Margunayasa; Dewa Bagus Sanjaya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aimed to develop a digital comic based on Don Bosco values and examine its validity, practicality, and effectiveness for third-grade elementary school students. The study used a research and development approach with the ADDIE model. It was conducted at Santo Petrus Private Elementary School, Medan, during the second semester of the 2025/2026 academic year. Five experts participated in product validation, two teachers and 25 students completed practicality questionnaires, and 31 students completed the pretest and posttest. Data were collected through observation, interviews, document analysis, expert validation sheets, response questionnaires, and learning outcome tests. The data were analyzed using percentage scores, mean scores, and normalized gain. The findings showed that the digital comic met highly feasible criteria, with media validation scores of 88.6% and 100%, material validation scores of 89.4% and 100%, and a language validation score of 90%. Teacher practicality scores were 91.67 and 89.00, while the students' mean response was 4.27, categorized as highly practical. The mean learning score increased from 61.11 on the pretest to 88.90 on the posttest. The N-Gain score was 0.71 or 71%, categorized as high. The study concludes that digital comics can provide a valid, practical, and effective medium for presenting Don Bosco values through visual, contextual, and student-friendly learning experiences.